Analisis Penggunaan Teknologi Digital : Building Information Modeling (BIM) dan Pemodelan 3D dalam Meningkatkan Keakuratan Desain Arsitektur - Jasmine Ramadhani; Retno Putri Rengganis (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
In the current digital era, technological advances are developing very quickly and have a big influence in various areas of life. One innovation that has received great attention in the architectural industry is BIM (Building Information Modelling) technology. BIM has fundamentally changed the way design and construction are done, having a major impact on improving the efficiency, quality and sustainability of the architectural process. Before BIM, architectural design generally relied on 2D drawings that required complex interpretation and coordination, which often led to errors and delays in construction projects. However, with advances in technology and the adoption of BIM, architects can now create fully integrated 3D digital models. Considering that the earth as a place where humans live has a three dimensional (3D) shape, the nned for 3D information has now become very important to support various human activities. Apart from that, technology continues to develop rapidly, including in the field of mapping, with the emergence of increasingly advanced photogrammetry technology.